Intrinsic curvature of HIV-1 CA hexamer underlies capsid topology and interaction with cyclophilin A - Ni, Tao (Nat Struct Mol Biol, 2020)
The mature retrovirus capsid consists of a variably curved lattice of capsid protein (CA) hexamers and pentamers. High-resolution structures of the curved assembly, or in complex with host factors, have not been available. By devising new cryoEM methodologies for exceedingly flexible and pleomorphic assemblies, we have determined cryoEM structures of apo CA hexamers and in complex with cyclophilin A (CypA) at near-atomic resolutions. The CA hexamers are intrinsically curved, flexible and asymmetric, revealing the capsomere, instead of previously touted dimer or trimer interfaces, as the key contributor to capsid curvature. CypA recognizes specific geometries of the curved lattice, simultaneously interacting with three CA protomers from adjacent hexamers via two non-canonical interfaces, thus stabilizing the capsid. By determining multiple structures from various helical symmetries, we further revealed the essential plasticity of the CA molecule that allows formation of continuously curved conical capsids and the mechanism of capsid pattern-sensing by CypA.